The Impact of Profit-Sharing System and Customer Trust on Customers' Saving Interest in Mudharabah Savings - Chintia Romadayanti; Ardini Putri Qiftiah; Purwati; Dewi Fadila (International Journal of Advanced Research in Social Studies, 2025)
This research aims to analyze the impact of the profit-sharing system and customer trust on customers' saving interest in Mudharabah savings at Bank Syariah Indonesia KC Palembang Demang. The research employs a quantitative approach with an experimental design. A total of 76 respondents, who are customers of BSI KC Palembang Demang using Mudharabah savings, were selected as the research sample using probability sampling with the Slovin formula. Data was collected through questionnaires and analyzed using SPSS version 25, with validity testing, reliability testing, t-test, F-test, determination coefficient (R2), correlation coefficient, and multiple linear regression. The results show that the profit-sharing system has a significant positive impact on customers' saving interest, while customer trust does not significantly affect saving interest. Additionally, both independent variables simultaneously have a significant positive impact on saving interest. This study suggests that BSI KC Palembang Demang should enhance the implementation of the profit-sharing system and strengthen customer trust to increase saving interest in Mudharabah savings.